MAKNA SIMBOL NILAI KEBANGSAAN DALAM PERAYAAN ERAU - Janah, Ulum; Rosdiana, Rosdiana; Indriastuty, Nina (Fakultas Ilmu Budaya, Universitas Mulawarman, 2018)
In local wisdom that has a fair value, the local community has an identity for the nationality of the country. These national values are the basis for national resilience because in these symbols there are patterns in supporting things and as a form of filtering for globalization and support for national resilience. This research aims to find out the national values through symbolic symbols in Erau traditional celebrations in Tenggarong as supporters of national resilience. Descriptive qualitative analysis with Peirce's semiotic approach to interpreting symbols in Erau celebrations that have national values. Its superiority is able to interpret symbols in the Erau context in various other fields. Erau as one of the cultural forms created by the people of Kutai Kartanegara has a symbol of nationality in every ritual in it. Overall, the indigenous people, in this case, the Kutai Kartanegara Sultanate in carrying out Erau is inseparable from the mythology they use based on the Salasilah of the Kutai Kartanegara Sultanate and also the Panji Selaten and Braja Niti books. Mythology is a cultural root that has been passed down from generation to generation as the identity of the Kutai Kartanegara Sultanate and also the patterns of life of its people. In addition, some of the rituals in Erau were designed by the Kutai Sultanate, as well as those that had rules, as a sultanate, they also had separate rules.